2013
DOI: 10.1097/sla.0b013e31826eda3b
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors After Pulmonary Metastasectomy for Colorectal Cancer and Rationale for Determining Surgical Indications

Abstract: We should utilize these prognostic factors to detect patients who might benefit from surgery. Therefore, we should periodically follow up advanced colorectal cancer patients by chest computed tomography to detect small pulmonary metastases before serum CEA elevation. Metastases to the lung or organs upstream from the lung are regarded as semi-local for colorectal cancer. This concept provides a rationale for validating surgical indications for pulmonary metastases from colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 18 publications
7
101
2
3
Order By: Relevance
“…In the study population, the number of liver metastases, the size of lung metastases, and the preoperative serum CEA levels were lower than in the medical population, which may have led to the favorable prognosis in the study population. Several series of lung resection have demonstrated factors predictive of survival in patients with colorectal lung metastases; 35,36 however, the factors vary widely among reports and no consensus is available to date regarding indications for lung resection. As suggested by our study, effective chemotherapy may further impact the prognosis of patients with colorectal lung metastases.…”
Section: Discussionmentioning
confidence: 98%
“…In the study population, the number of liver metastases, the size of lung metastases, and the preoperative serum CEA levels were lower than in the medical population, which may have led to the favorable prognosis in the study population. Several series of lung resection have demonstrated factors predictive of survival in patients with colorectal lung metastases; 35,36 however, the factors vary widely among reports and no consensus is available to date regarding indications for lung resection. As suggested by our study, effective chemotherapy may further impact the prognosis of patients with colorectal lung metastases.…”
Section: Discussionmentioning
confidence: 98%
“…15,[21][22][23] The pre-thoracotomy CEA level was the most prognostic factor for survival in a multivariate analysis, and has been reviewed in other reports. 34,35) It has been reported that 70% of patients with recurrent or metastatic colorectal carcinoma are CEA-positive. 36) The indications for surgery should be considered carefully in these "high-risk" patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a worse prognosis after lung metastasectomy in patients with hilar/mediastinal lymph node metastasis [5, 18, 20, 21]. However, it still remains uncertain whether those patients benefit from lung metastasectomy along with lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%